Decellularization of porcine kidney with submicellar concentrations of SDS results in the retention of ECM proteins required for the adhesion and maintenance of human adult renal epithelial cells. (6th May 2022) - Bongolan, Tonya; Whiteley, Jennifer; Castillo-Prado, Jorge; Fantin, Amanda; Larsen, Brett; Wong, Cassandra J.; Mazilescu, Laura; Kawamura, Masataka; Urbanellis, Peter; Jonebring, Anna; Salter, Eric; Collingridge, Graham; et al.
Abstract : When decellularizing kidneys, it is important to maintain the integrity of the acellular ECM, including associated adhesion proteins and growth factors that allow recellularized cells to adhere and migrate according to ECM specificity. Abstract : When decellularizing kidneys, it is important to maintain the integrity of the acellular extracellular matrix (ECM), including associated adhesion proteins and growth factors that allow recellularized cells to adhere and migrate according to ECM specificity. Kidney decellularization requires the ionic detergent sodium dodecyl sulfate (SDS); however, this results in a loss of ECM proteins important for cell adherence, migration, and growth, particularly glycosaminoglycan (GAG)-associated proteins. Here, we demonstrate that using submicellar concentrations of SDS results in a greater retention of structural proteins, GAGs, growth factors, and cytokines. When porcine kidney ECM scaffolds were recellularized using human adult primary renal epithelial cells (RECs), the ECM promoted cell survival and the uniform distribution of cells throughout the ECM. Cells maintained the expression of mature renal epithelial markers but did not organize on the ECM, indicating that mature cells are unable to migrate to specific locations on ECM scaffolds.